Mother Empowerment through Family-Based Child Health Education - Alfrianne Alfrianne; Elisabeth Surbakti; Maida Pardosi; Efendi Sianturi (Indonesian Journal of Global Health Research, 2025)
The role of parents (family) and caregivers is an important key in the growth and development of children, becoming the initial seed of a nation as the next generation becomes a better, dignified, and stronger nation. The future of a nation lies in the hands of children ad, adolescents, and adults, so it is necessary to empower mothers based on families. Objective: The aim is to improve the knowledge and attitudes of mothers with children aged 0-5 years by empowering mothers about child health education in child care patterns in families in Saentis Village, Deli Serdang Regency. Method: This study is quasi-experimental to improve mothers' knowledge and attitudes about family-based child-rearing patterns. Health promotion by PKK mothers who are Family Welfare Empowerment are trained to become agents of Change. The measuring instrument is a questionnaire. A sample of 50, namely mothers with children (0-5 years) (n = 50). Data analysis using the Paired T-test if the data is usually distributed, and if the data is not normally distributed, the Wilcoxon test is used. Results: This study shows a difference in the average; there is an increase in the knowledge and attitudes of mothers with children aged 0-5 years towards child health education in child care patterns in the family p-value = 0.001. Conclusions High maternal education impacts investment in quality human resources because, with maternal education, the nutritional status of toddlers will increase and ultimately can increase the educational opportunities for their toddlers as essential capital for increasing quality human resources.